INTEGRATION OF THE VALUE OF RELIGIOUS MODERATION IN ISLAMIC EDUCATION CURRICULUM - Ruslan, Ruslan; Luthfiyah, Luthfiyah (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2026)
This paper aims to analyze the integration of the value of religious moderation in the Islamic education curriculum as a strategic effort in building inclusive, tolerant, and civilized religious attitudes in the midst of a pluralistic society. Religious moderation is understood as a religious attitude that prioritizes balance, justice, and rejection of extremism, so it is relevant to be internalized in the Islamic education system. This study examines the concept of religious moderation from theological, social, and pedagogical perspectives, and examines the dynamics of the Islamic education curriculum in responding to global and local challenges. The results of the discussion show that the integration of the value of religious moderation can be carried out through strengthening learning objectives, developing contextual teaching materials, applying dialogical and reflective learning methods, and an evaluation system that emphasizes affective and social aspects. In addition, the role of teachers as agents of moderation, strengthening school culture, and implementing hidden curriculum are key factors in the success of internalizing the value of religious moderation. This integration has been proven to contribute to the formation of moderate student character, increasing tolerance, and strengthening democratic values and diversity. Therefore, religious moderation needs to be placed as a conceptual and operational foundation in the development of an Islamic education curriculum that is adaptive to the changing times. The implications of this study emphasize the importance of policy support, strengthening the capacity of educators, and developing a moderation-based learning model to realize Islamic education oriented towards social harmony and mutual benefit.